EFFECTS OF CAPITAL BASE ON SHAREHOLDERS’ WEALTH OF KENYAN LISTED COMPANIES INVOLVED IN MERGERS AND ACQUISITIONS - Kioko, Muange Samson; Kiweu, Josephat Mboya; Nzioki, Susan (International Journal of Economics, Commerce and Management, 2018)
The study sought to establish the effect of capital base on the shareholders’ wealth of Kenyan listed firms involved in Mergers and Acquisitions (M&A). The study adopted a descriptive research design. Comparisons were made between the mean of 3 years pre-merger/acquisition and 3 years post-merger/acquisition financial ratio while the year of merging and period of acquisition were exempted. The study found that the performance of the Kenyan companies in shareholders wealth was on average the same following the M&A. In addition, performance in capital base was on average the same before and after M&A. Furthermore, the study established that an increase in capital base will lead to a significant increase in shareholders’ wealth. The study recommends that management should not only undertake M&A in order to improve operation and sustain failing businesses but also improve their competitiveness and financial standing. In addition, management should come up with a sound strategy towards asset and liability management so as to avert the problem of mismatching investments and also the quality of assets should be enhanced. Management should put into consideration the degree of transferability and marketability of assets invested in so that the assets can provide liquidity to the firm with ease.
Keywords: Capital base, mergers and acquisitions, shareholders wealth, listed companies